Impact of remittances on schooling in the Philippines: Does the relationship to the household head matter? - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2011)
The remittance have emerged as one of the most important sources of international flows. In the Philippines, the amount of remittance receipts has more than doubled over a decade since early 1990s. As a result, the way remittances are used has become extremely important for economic development. Unlike the previous studies, we allow for the potential heterogeneity in the impact of remittances across various relationships to the head of household and take into account the potential negative effects of being guarded by someone other than the parents. We find that the impact of remittances on schooling is generally positive and the negative impact is outweighed by the positive impact of remittance flows.